Nagarkar : inter-departmental correspondence - Bolton, W. J.
032-0035-001 I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From W.J. Bolton. To Sir Walter Citrine. Department International. Date 26th June, 1939. SUBJECT. NAGARKAR. Joshi writes enclosing a letter he has sent to Nagarkar, stating that the passage will cost £40 by P.& O. line, but £30 if he (Nagarkar) makes use of the cheapest passage. Joshi in his letter to us asks what the terms are under which Nagarkar will receive training. We told Joshi £250 per annum in a letter to him (15 February, 1938). Perhaps Joshi is asking in an Eastern fashion for a further advance. Are you willing to send him say £20 more for Nagarkar? AT/1055 26/6/39 W.J. Bolton 292/946/32/35